Tear secretion by Diquafosol suppresses the excitability of trigeminal brainstem nuclear complex neurons by reducing excessive P2Y2 expression in the trigeminal ganglion in dry eye rats. (June 2023) - Katagiri, Ayano; Tsubota, Kazuo; Mikuzuki, Lou; Nakamura, Shigeru; Toyofuku, Akira; Kato, Takafumi; Bereiter, David A.; Iwata, Koichi
Abstract: The P2Y2 receptor agonist, diquafosol sodium, is commonly used to treat the signs and symptoms of dry eye disease (DE) patients. Although diquafosol improves tear film stability, the neural mechanisms underlying the reduction in ocular pain are not well defined. This study determined if repeated application of diquafosol reduces the sensitization of nociceptive neurons in the lower trigeminal brainstem nuclear complex (TBNC) via peripheral P2Y2 mechanisms in a rat model for DE. Diquafosol was applied to the ocular surface daily for 28 days, starting at day 0 or day 14, after exorbital gland removal. The number of eyeblinks, P2Y2 -immunoreactive neurons in the trigeminal ganglion (TG), and correlates of TBNC neural excitability (i.e., cFos protein and phosphorylated extracellular signal-regulated kinase (pERK) expression) were assessed in male rats. Diquafosol increased spontaneous tear volume and reduced the number of ocular surface-evoked eyeblinks in DE rats. Fluorogold-labeled TG neurons that supply the cornea expressed P2Y2 . The number of P2Y2 -immunoreactive neurons was increased in DE rats and suppressed by diquafosol. Diquafosol also reduced the number of cFos- and pERK-immunoreactive neurons in the TBNC in DE rats. These findings suggest that diquafosol, regardless of late-phase treatment, relieves ocular nociception in DE by reducing peripheral P2Y2 expression. Highlights: The P2Y2 receptor agonist, diquafosol sodium, enhanced tear volume in dry eye rats. Diquafosol sodium (Dq) decreases P2Y2 expression in the TG of dry eye rats. TG neurons innervating to the cornea express P2Y2 . Dq attenuates corneal hypersensitivity in dry eye regardless of the treatment phase. Dq attenuates central sensitization of neuronal activity in dry eye.